PENGARUH KEMISKINAN DAN TINGKAT PENGANGGURAN TERBUKA TERHADAP INDEKS PEMBANGUNAN MANUSIA DI PROVINSI JAWA TIMUR TAHUN 2018 - Alie Sadikin; Rusmasari Rusmasari (Develop: Jurnal Ekonomi Pembangunan, 2022)
The purpose of this study is to explain the effect of poverty and the open unemployment rate on economic growth in the province of East Java with the period used is 2018. Quantitative is the type of research with a total sample of 38. The data used are secondary data obtained on the official website of the Central Statistics Agency of East Java Province. The method of data analysis used a Descriptive Statistical Test, used Classical Assumption Test, and also used Hypothesis Testing. The conclusion from the results of this test is (1) Poverty has a negative effect to the Human Development Index (HDI), namely -7.831 < 2.030 and sig value of 0.000 < from 0.05, (2) Open Unemployment Rate (TPT) does not have a positive effect. the Human Development Index (HDI) is 1.822 < 2.030 and a sig value of 0.077 > from 0.05, (3) Poverty and the Open Unemployment Rate (TPT) are 68.4% while the remaining 31.6% is influenced by other variables outside of Research Model.